2016
DOI: 10.1080/19443994.2015.1040853
|View full text |Cite
|
Sign up to set email alerts
|

Simplification and sensitivity study of Alamar Blue bioassay for toxicity assessment in liquid media

Abstract: A B S T R A C TBacteria, as an essential component of most wastewater treatment plants (WWTPs), play a critical role in the biological stage of WWTPs due to their role in cycling mineral compounds and in the decomposition of organic material. In this study, a modified Alamar Blue-based bioassay was used to evaluate the toxicity of metal plating wastewaters on sequence batch reactor (SBR) bacteria. For confirming the robustness, reproducibility, and efficiency of the optimized method, it was compared with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…2020; 9(1):e83067. (12)(13)(14)(15)(16). However, according to the results of this study, the complete degradation of insecticides to H 2 O and CO 2 normally takes place un-der special conditions (18).…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…2020; 9(1):e83067. (12)(13)(14)(15)(16). However, according to the results of this study, the complete degradation of insecticides to H 2 O and CO 2 normally takes place un-der special conditions (18).…”
Section: Resultsmentioning
confidence: 48%
“…In the last decades, there has been great attention to the development of efficient methods for insecticide removal from aqueous environments based on advanced ox-idation processes (AOPs) such as TiO 2 /Ni photo-electrode (2), UV/N-doped TiO 2 nanosheets (3), UV/iodide/ZnO (9), UV/H2O2 (10), and UV/nano-ZnO (11). Among such processes, UV/nano-ZnO can be regarded as an effective treatment method for hazardous contaminants such as diazinon, malathion, and other compounds (12)(13)(14)(15)(16). However, the complete mineralization of such contaminants to H 2 O and CO 2 normally needs different parameters such as contact time, anionic and cationic concentration, initial concentration of pollutants, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a direct and positive relationship between the inhibition percentage of the activity of dehydrogenase enzyme of the bacteria and inhibition percentage of the colonies that formed (R 2 = 0.987). In the study by Zare et al ( 2016 ), RR method and its comparison with CFU of Pseudomonas, Enterobacter, and Bacillus bacteria were evaluated in determining the toxicity of wastewater containing heavy metals. In their study, it was found that there is a linear and direct relationship between the bacterial enzymatic activity and colony count in determination of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Following 60 min of contact time, 2 mL of HCl-phthalate 0.05 M buffer and 20 mL of n-amyl alcohol solution were added to each test tube. Afterwards these materials were stirred slowly, The rate of alamar blue reduction was determined through the extent of absorption at the wavelength of 620 nm using UV/ViS spectrophotometer device (Braic 2100) (Toolabi et al 2017; Zare et al 2016). The percentage of alamar blue reduction was obtained using Eq.…”
Section: Methodsmentioning
confidence: 99%
“…But in the presence of living bacteria, alamar blue is converted to resorufin and the color of the solution changes from blue to pink (Nasiry et al 2007; Rampersad 2012; Gregoraszczuk et al 2015; Balouiri et al 2016; Tyc et al 2016; Zare et al 2016; Teh et al 2017; Toolabi et al 2017). To achieve the best and most effective method of removal and risk assessment of diazinon in aqueous solution, more studies need to be done in this regard.…”
Section: Introductionmentioning
confidence: 99%